The effect of educational gymnastics on postural control of young children - Anderson, Neil; Button, Chris; Lamb, Peter (Frontiers in Psychology, 2022)
Fundamental movement skill (FMS) proficiency does not develop solely due to maturation, but also via diverse perceptual-motor experiences across childhood. Practicing gymnastics has been shown to improve postural control. The purpose of the present study was to examine potential changes to postural control of children following a course of educational gymnastics. Two groups of children both completed 20 × 45-min physical education (PE) lessons; one group (n = 43, age = 6.4 ± 0.7, 56% male) completed educational gymnastics lessons in school delivered by a professional coach, the other group completed their typical PE classes (n = 18, age = 6.5 ± 0.3, 33% male). Unipedal balancing performance was assessed by calculating the percentage of successful trials made. Postural sway dynamics were explored by calculating center-of-pressure sample entropy, 95% ellipse sway area and sway velocity. Measurements were taken before the lessons began and immediately after the lessons were completed. The gymnastics group performed better than the typical PE group at unipedal balancing. Females outperformed males in both groups. Males made different changes to postural control (i.e., increased sway regularity and improved stability) compared to females across 3 months. Educational gymnastics enabled children in a critical period of development to make more rapid improvements to postural performance and control. Novel movement experiences, like those offered by educational gymnastics, may have a positive influence on postural control and importantly, physical literacy. Future work should examine how sex effects the development of postural control strategies in young children.